2018
DOI: 10.1093/pubmed/fdx188
|View full text |Cite
|
Sign up to set email alerts
|

The nature and frequency of abdominal symptoms in cancer patients and their associations with time to help-seeking: evidence from a national audit of cancer diagnosis

Abstract: BackgroundRaising awareness of possible cancer symptoms is important for timely help-seeking; recent campaigns have focused on symptom groups (such as abdominal symptoms) rather than individual alarm symptoms associated with particular cancer sites. The evidence base supporting such initiatives is still emerging however; understanding the frequency and nature of presenting abdominal symptoms among cancer patients could inform the design and evaluation of public health awareness campaigns.MethodsWe examined eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 34 publications
2
31
0
Order By: Relevance
“…Previous work using the NCDA has shown significant variation in the patient interval (symptom onset to presentation) by different abdominal symptoms,24 and cohort studies have shown similar variation of different diagnostic intervals by symptoms for patients with colorectal,25 lung26 and pancreatic cancer 27. Other studies using linked primary care data have found longer diagnostic intervals (from symptom presentation to diagnosis) for those presenting with non-alarm symptoms5 28 29 when compared with alarm symptoms patients.…”
Section: Discussionmentioning
confidence: 95%
“…Previous work using the NCDA has shown significant variation in the patient interval (symptom onset to presentation) by different abdominal symptoms,24 and cohort studies have shown similar variation of different diagnostic intervals by symptoms for patients with colorectal,25 lung26 and pancreatic cancer 27. Other studies using linked primary care data have found longer diagnostic intervals (from symptom presentation to diagnosis) for those presenting with non-alarm symptoms5 28 29 when compared with alarm symptoms patients.…”
Section: Discussionmentioning
confidence: 95%
“…We believe that past literature on self-care behaviors before diagnosis and the emerging evidence supports this research agenda. For instance, a recent study on the nature and the frequency of abdominal symptoms suggest that patients with persistent bloating and distention waited a minimum of two months before presenting to primary care [27]. The identification of self-care behaviors using commercial data could be an effective approach to probe earlier engagement in primary care.…”
Section: Discussionmentioning
confidence: 99%
“… 76 , 88 , 89 Symptoms associated with the longest patient intervals (time from symptom onset to presentation) may also be particularly worthy of targeting. 90 …”
Section: Symptom Epidemiologymentioning
confidence: 99%